Quintuple Helix Model dalam Pengembangan Desa Wisata Lorong Mari Kota Palembang - Sutinah, Sutinah; Iriani, Atrika; Zubaidah, Siti (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2023)
The aim of this research is to analyze the Quintuple-Helix Model in the Development of the Lorong Mari Tourism Village. Every country is currently focusing on developing tourism, considering its impact on economic growth and social welfare. Lorong Mari is an area with diverse tourist destinations. The majority of tourist destinations in the Lorong Mari Tourism Village promote the creation of colorful aisles as tourism icons, including tourist village destinations. However, tourist villages in the city have not received full attention from tourists. Therefore, it is necessary to find a solution to optimize tourism management and increase the number of tourist visits significantly through interactions between the government, tourism industry, universities, media, society and the environment in managing tourist villages in the Lorong Mari Tourism Village, hence the framework in the research This uses three indicators, namely knowledge, innovation and tourism sustainability according to Carayanis and Campbell (2010). The analysis techniques used include: Data Condensation, Data Display, and Conclusion Drawing/Verifications. This research is divided into 3 (three) stages. First primary and secondary data collection through interviews, observation and documentation. The results of the discussion explained that management of tourist villages requires synergistic interaction from several elements including government, tourism industry, universities, media, society and the environment. This interaction can at least be a solution in improving the quality of tourism village management. With the government, tourism industry, universities, media, society and the environment interacting with each other, the management of the Lorong Mari Tourism Village becomes more optimal and attracts more tourists to visit.